Cardiometabolic factors and vitamin D deficiency in pediatric patients with chronic kidney disease - Parra-Ortega, Israel; Zurita-Cruz, Jessie Nallely; Villasis-Keever, Miguel Angel; Klünder-Klünder, Miguel; Vilchis-Gil, Jenny; Zepeda-Martinez, Carmen; Rizo Romero, Ángeles; Alegria-Torres, Gabriela; Romero-Navarro, Benjamin; Romo-Vázquez, José Carlos (Frontiers in Nutrition, 2024)
Background: Patients with chronic kidney disease (CKD) are at increased risk for cardiovascular disease. Up to 80% of patients with CKD may exhibit inadequate vitamin D (VD) levels, which have been linked to the presence of cardiometabolic factors (CFs) in the adult population. However, research on this association in the pediatric population is limited. Objective: To analyze the effects of 25-hydroxyvitamin D3 (25-[OH]D) levels and status on the presence of CFs in children receiving kidney replacement therapy (KRT). Materials and Methods: This cross-sectional study included pediatric patients receiving KRT, aged 8 to 17 years, who were receiving hemodialysis or peritoneal dialysis from January 2021 to March 2024. We conducted anthropometric measurements, blood pressure assessments, and glucose, 25-(OH)D, and lipid profiling for all participants. The daily dose of cholecalciferol supplementation, as well as other medications affecting bone and lipid metabolism and antihypertensive drugs, were documented. Statistical analyses were performed using Student's t tests and chi-square tests to compare the CFs between groups with and without VD deficiency. Results: The study involved 156 patients with an average age of 12.9 years and a mean serum VD level of 22.5 ng/dL. Patients with VD deficiency presented higher levels of total cholesterol and diastolic blood pressure (p < 0.05). No statistically significant differences were found in other biochemical profile variables or in the frequency of cardiometabolic factors. Conclusions: vitamin D deficiency seems to increase the risk of dyslipidemia and uncontrolled hypertension in children and adolescents with end-stage CKD.